2005
DOI: 10.2464/jilm.55.582
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cr content on phase constitution, electrical resistivity and vickers hardness in quenched Ti-Cr alloys

Abstract: As basic study to develop low cost b Ti alloys, changes in phase constitution, electrical resistivity and Vickers hardness with increase of Cr content were investigated in Ti-Cr binary alloys quenched from 1173 K. In solution treated and quenched state, hexagonal martensite, aЈ was identified at 3Cr and 5Cr alloys, whereas b phase was identified from 5Cr to 20Cr. In 7Cr and 10Cr alloys, athermal w was also identified. Resistivity increased with increase of Cr content up to 10 mass% Cr and then slightly decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…In addition, the maximum in microhardness at 10 mass% chromium is believed to be a result of the strengthening/hardening effect of ω-phase. This is in agreement with previous results using Ti-7Cr 13,22) . The yield strength, tensile strength, and elongation of the Ti-Cr alloys with 15 or 20 mass% chromium in this study (888-873, 905-898 MPa, and 12% each) get the better of those of hardened Type 4 gold-base alloys (493-825, 690-830 MPa, and 1-12%) and Co-Cr alloys (500-710, 650-870 MPa, and 2-12%) [23][24][25][26] .…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In addition, the maximum in microhardness at 10 mass% chromium is believed to be a result of the strengthening/hardening effect of ω-phase. This is in agreement with previous results using Ti-7Cr 13,22) . The yield strength, tensile strength, and elongation of the Ti-Cr alloys with 15 or 20 mass% chromium in this study (888-873, 905-898 MPa, and 12% each) get the better of those of hardened Type 4 gold-base alloys (493-825, 690-830 MPa, and 1-12%) and Co-Cr alloys (500-710, 650-870 MPa, and 2-12%) [23][24][25][26] .…”
Section: Discussionsupporting
confidence: 83%
“…According to a previous report, addition of chromium to titanium causes a phase transition from α-phase to β-phase. As described above, Ikeda et al 22) suggested that the development of ω-phase increased hardness and Koike et al 13) noted that ω-phase decreased ductility. The increase in hardness was probably caused by the solidsolution hardening of the α-phase or the β-phase.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…It has been reported that the reverse transformation from 00 (orthorhombic) phase to the phase causes shape recovery to appear. [17][18][19] Ti-Cr is also hopeful alloy system for biomedical applications and there are some reports on mechanical properties of Ti-Cr 20,21) and Ti-Cr-X alloys. [22][23][24][25] Selection of Ti-Cr-Sn alloy system was due to phase stabilizing effect of Cr, low melting points of Cr and Sn as compared to other phase stabilizing elements and solid solution strengthening effect of Cr and Sn (atomic radius: Cr ¼ 0:126 nm, Sn ¼ 0:158 nm, Ti ¼ 0:146 nm).…”
mentioning
confidence: 99%
“…5 (a)), a significant increase in hardness was observed after heat treatment at 873-973 K and maximum hardness was obtained after heat treatment at 973 K. Under these conditions, athermal ω formed in these alloys after quenching, and its amount was larger in the alloy heat-treated at 973 K. Athermal ω is reported to increase the hardness of Ti alloy. [13,14] Therefore, this study suggests that an increase in hardness of these alloys was caused by the formation of athermal ω. No significant increase in hardness was observed in the alloys with oxygen content of 0.75 and 1 mass%.…”
Section: T β (K) = 1155 + 232[o] -84[nb]mentioning
confidence: 70%